Sign Language Research, Uses and Practices: Crossing Views on Theoretical and Applied Sign Language Linguistics - Meurant, Laurence; Sinte, Aurélie; Van Herreweghe, Mieke; Vermeerbergen, Myriam (De Gruyter, 2013)
Sign Language; Applied Linguistics; Intercultural Communication